Determination of nutrient digestibility in corn and soybean meal using the direct and substitution methods as well as different basal diets fed to growing pigs. Issue 1 (1st January 2019) - Liu, Dewen; Liu, Hu; Li, Defa; Wang, Fenglai
ABSTRACT: Two experiments were conducted to compare methods of determination of the apparent total tract digestibility (ATTD) of various chemical constituents in corn and soybean meal (CS) when fed to growing pigs. Expt. 1, eighteen barrows (34.3 ± 1.1 kg) were randomly allotted to 1 of 3 diets. The three diets were Corn, CS-Basal, and CS-Test. The ATTD of DM, GE, CP, and organic matter (OM) in corn determined by the direct method were not different from those determined by the substitution method. Expt. 2, twenty-four barrows (36.2 ± 1.4 kg) were randomly allotted to 1 of 4 diets. The four diets were Basal diet 1 (97.5% corn), Test diet 1(replaced corn in Basal diet 1 with 15% SBM), Basal diet 2 (72.5% corn and 25% SBM), and Test diet 2 (58% corn and 39.5% SBM). The ATTD of GE and CP of SBM were greater ( p  < 0.05) determined by the Corn-Basal diet method than Corn-SBM-Basal diet method. In summary, there was no difference in the ATTD of nutrients in corn when determined using direct or substitution method, but the ATTD of GE and CP in SBM determined using the Corn-Basal diet method were greater than using Corn-SBM-Basal diet method.